The Use of Divine Names in Rural Baetic Areas - Alvar Ezquerra, Jaime; Pañeda Murcia, Beatriz (ARYS. Antigüedad: Religiones y Sociedades, 2021)
This paper analyses the divine onomastic sequences documented in the rural epigraphy of Baetica by applying the taxonomy of divine epithets developed within the EPIDI project. The aim is to determine whether or not the use of these onomastic formulae is independent of the usage found in the cities and, consequently, whether they reveal religious behaviours specific to the countryside that would allow us to speak of a rustic religious praxis, or whether, on the contrary, they reflect an orthopraxis determined by urban religion. To this end, we conduct, firstly, a comparative study of the gods and epithets attested in the urban zones and in the rural areas of the province. Secondly, we examine the most singular deities and epithets from the rural milieu taking into account the circumstances that may have motivated the worshippers’ choice of the deities and the divine appellatives concerned.